Dukungan Sosial Keluarga Terhadap Resiliensi pada Narapidana di Lembaga Pemasyarakatan Klas IIA Kupang - Sarlina Kurniati Tunliu; Diana Aipipidely; Feronika Ratu (Journal of Health and Behavioral Science, 2019)
Resilience is an individual capability to survive and overcome the difficulties or pain, also be able to raise up from that situation. One of the factors that can help individuals achieve resilience is social support, especially family support, as a family is a primary environment in which certain roles and functions exist. This study aims to investigate the effect of family social support on resilience in prisoners in Kupang ClassIIA Correctional Institution. The type of research is quantitative with an analytic survey method using a cross-sectional research design. The study sample is 81 inmates which were collected using the purposive sampling technique. The measures used in this study were the family social support scale (54 valid items; α= .921), and the resilience scale (49 valid items; α= .900). The simple linear regression analysis revealed a positive and significant effect between family social support and inmate's resilience (.420; p < .05 measured with the resilience scale). In addition, family social support contributed 47,2%, this means that family social support is not a dominant factor affecting resilience in prisoners in Kupang Class IIA Correctional Institution.